Pengaruh Back Rub Terhadap Nyeri Punggung Dan Kualitas Tidur Ibu Hamil Trimester III - Nawati Nawati; Ningning Sriningsih; Yuliati Amperaningsih; Idawati Manurung (Malahayati Nursing Journal, 2022)
ABSTRACT Pregnant women in the third trimester often experience back pain due to physiological changes in the enlargement of the abdomen and fetus that put pressure on the muscles, bones, joints, resulting in sleep disturbances and poor sleep quality. The purpose of this study was to determine the effect of Back rub on back pain and sleep quality of third trimester pregnant women. The research location is at the Bogor City Health Center. This type of quantitative research uses a quasi-experimental method with a pre post test approach with control group design. Respondents, third trimester pregnant women were 30 people in the intervention group and 30 people in the control group. sampling method using purposive sampling. The results, back rub did reduce back pain and improve the quality of sleep and health education programmed and structured to help pregnant women understand and make it easier to apply information at home. The researcher's suggestion is that health education programs and back rub knowledge must be taught to pregnant women from the beginning of pregnancy, every time pregnancy control is at the Puskesmas Keywords: back rub, back pain, sleep quality ABSTRAK Ibu hamil trimester ke III sering mengalami nyeri punggung karena perubahan fisiologis pembesaran perut dan janin yang menekan otot, tulang, sendi sehingga mengakibatkan gangguan tidur dan tidurnya menjadi tidak berkualitas. Tujuan penelitian untuk mengetahui pengaruh Back rub terhadap nyeri punggung dan kualitas tidur ibu hamil trimester III. Lokasi penelitian di Puskesmas Wilayah Kota Bogor.  Jenis penelitian kuantitatif yang menggunakan metoda kuasi eksperimen dengan pendekatan pre post test with control group desain. Responden, ibu hamil trimester tiga berumlah 30 orang kelompok intervensi dan 30 orang kelompok kontrol. metode pengambilan sampel menggunakan purposive sampling. Hasil, back rub memang menurunkan nyeri punggung dan meningkatkan kualitas tidur dan pendidikan kesehatan yang terprogram dan terstruktur membantu ibu hamil mengerti dan memudahkan untuk menerapkan informasi di rumah. Saran peneliti adalah program pendidikan kesehatan dan pengetahuan back rub wajib diajarkan pada ibu-ibu hamil sejak awal kehamilan, setiap kali kontrol kehamilan ke Puskesmas. Kata Kunci: Back Rub, Nyeri Punggung, Kualitas Tidur